2006
DOI: 10.1136/bjo.2006.090951
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective performance of the Lenstec KH-3500 "accommodative" intraocular lens

Abstract: Aim: To determine whether eyes implanted with the Lenstec KH-3500 ''accommodative'' intraocular lenses (IOLs) have improved subjective and objective focusing performance compared to a standard monofocal IOLs. Methods: 28 participants were implanted monocularly with a KH-3500 ''accommodative'' IOL and 20 controls with a Softec1 IOL. Outcome measures of refraction, visual acuity, subjective amplitude of accommodation, objective accommodative stimulus response curve, aberrometry, and Scheimpflug imaging were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…Other subjective measures of efficacy, such as spectacle independence and reading speeds, 16,24 favored accommodating IOLs, whereas there was no difference in glare and contrast sensitivity. 18,21,24 No secondary measure of efficacy was reported by more than 3 studies. The single objective measure, pilocarpine-induced anterior shift, consistently favored the accommodating IOLs; however, the clinical relevance of the findings was unclear.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other subjective measures of efficacy, such as spectacle independence and reading speeds, 16,24 favored accommodating IOLs, whereas there was no difference in glare and contrast sensitivity. 18,21,24 No secondary measure of efficacy was reported by more than 3 studies. The single objective measure, pilocarpine-induced anterior shift, consistently favored the accommodating IOLs; however, the clinical relevance of the findings was unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Based on 10 trials of 508 eyes, [14][15][16][17][18][20][21][22]24 accommodating IOLs improved DCNVA more than monofocal IOLs; the standardized mean difference was À1.36 (95% CI, À2.22 to À0.49); however, the substantial heterogeneity across studies (I 2 Z 94%) could not be explained by any characteristic of the study population or methodology (Figure 2). Pooling the 6 homogeneous trials (I 2 Z 43%) of 179 total eyes showed no significant difference in DCNVA; the standardized mean difference was À0.16 (95% CI, À0.56 to 0.25) (Figure 2).…”
Section: Primary Efficacy Outcome: Distance-corrected Near Visual Acuitymentioning
confidence: 90%
“…8 Several single-optic IOL models have been developed. It was shown that the near visual outcomes with the preliminary IOL models were limited, [18][19][20][21][22][23][24][25] which was the main reason for the development of new accommodating IOL models. One example is the dual-optic IOL 26 and the new generation of single-optic accommodating IOL.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] Although subjective clinical assessments suggest high levels of patient satisfaction and good visual performance, 14,[24][25][26] objectively measured accommodative performance with these procedures have been disappointing. 16,[27][28][29] Subjective accommodation testing, such as the routinely used clinical push-up test, is inappropriate for unequivocally demonstrating an accommodative optical change in the power of the eye. 7,30 Subjective tests do not differentiate between passive depth of field due to small pupils and ocular aberrations and active accommodative power change in the eye.…”
mentioning
confidence: 99%